Treatment of Labial Mucocele by Intralesional Injection of Dexamethasone: Case Series - Maryam Baharvand; Shabnam Sabounchi; Hamed Mortazavi (Mashhad University of Medical Sciences, 2014)
Salivary mucocele is a common lesion derived from minor salivary glands with various surgical or non-surgical treatment modalities. To evaluate the effect of a highly potent corticosteroid (dexamethasone) in the management of salivary mucocele, we performed intralesional injection of dexamethasone in nine patients with labial mucocele. Complete healing of lesions observed in seven of nine patients, and size reduction in two of them. No local scarring or deformity of the lower lip occurred in any of the patients. One patient reported local discomfort at the site of injection. Intralesional injection of dexamethasone is a potentially curative method in the treatment of mucocele.